The cardiovascular epidemic with particular emphasis on the Muslim world - Rashid, ARA (Bangladesh Journal of Medical Science, 2011)
DOI: http://dx.doi.org/10.3329/bjms.v10i2.7800 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.65-71